Energy based method for numerical fatigue analysis of multidirectional carbon fibre reinforced plastics. (April 2015) - Wagner, P.; Bruder, T.; van Paepegem, W.; May, M.
Abstract : This paper describes experiments on multiaxial fibre reinforced plastic laminates, which were performed to obtain calibration data for numerical fatigue analyses. For this purpose, fatigue tests of laminates with multidirectional layers subjected to constant amplitude and block loading (0 ≤ R < 1 or R >1) were analysed. The presented simulation results display the fatigue behaviour of carbon fibre reinforced plastics for unidirectional loading conditions and a selected laminate.